The Unwritten Principle of Democracy - Pal, Michael (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2019)
This article considers the content of the unwritten principle of democracy and its potential relevance in Canadian constitutional interpretation. The unwritten principles of federalism, the rule of law and constitutionalism, democracy, and the protection of minorities set out by the Supreme Court of Canada in the Secession Reference have received extensive academic attention. Much yet remains unknown, however, about the democracy principle. This article argues that we should interpret the unwritten principle as embodying a “thin” or procedural account of democracy tied to meaningful participation, rather than a “thick” version imposing specific outcomes or broader obligations. I argue that whatever the weight of a “thick” account of democracy, a “thin” understanding is preferable for filling in the content of a constitutional principle that has legal force. The central critiques of the use of unwritten principles in constitutional interpretation are 1) that they lack legitimacy and 2) that they are incoherent in relation to one another. Operationalizing a thin version of democracy in constitutional interpretation responds better to the claims that the unwritten principles lack legitimacy or are incoherent. A thin account still permits the unwritten principle to carry out its functional role in constitutional interpretation, such as enabling courts to fill in gaps in the text or to engage in structural reasoning. The article considers the implications of this approach for referendums and municipal elections.